Close packing effects on clean and dirty snow albedo and associated climatic implications. Issue 8 (24th April 2017) - He, Cenlin; Takano, Yoshi; Liou, Kuo‐Nan
Abstract: Previous modeling of snow albedo, a key climate feedback parameter, follows the independent scattering approximation (ISA) such that snow grains are considered as a number of separate units with distances longer than wavelengths. Here we develop a new snow albedo model for widely observed close‐packed snow grains internally mixed with black carbon (BC) and demonstrate that albedo simulations match closer to observations. Close packing results in a stronger light absorption for clean and BC‐contaminated snow. Compared with ISA, close packing reduces pure snow albedos by up to ~0.05, whereas it enhances BC‐induced snow albedo reduction and associated surface radiative forcing by up to 15% (20%) for fresh (old) snow, with larger enhancements for stronger structure packing. Finally, our results suggest that BC‐snow albedo forcing and snow albedo feedback (climate sensitivity) are underestimated in previous modeling studies, making snow close packing consideration a necessity in climate modeling and analysis. Plain Language Summary: Snow plays a critically important role in the Earth climate system and water cycles. It affects not only surface radiative and heat fluxes but also freshwater resources. Previous modeling of snow albedo, a key climate feedback parameter, follows the independent scattering approximation. However, observations have shown that densely packed snow grains (i.e., close packing) are ubiquitous, where the independent scattering among grains may be invalid. This study, for the first time, explicitly accounts for close packing of snow grains and assesses its effects on clean and contaminated snow albedos by developing a new snow albedo model with internal mixing of aerosol and snow grains. We find that compared with the conventional independent scattering approximation, close packing reduces pure snow albedo and also enhances snow albedo reduction caused by black carbon contamination, with larger enhancements for stronger structure packing. Our results suggest that it is imperative to include snow close packing in climate modeling and analysis in order to improve the estimate of black carbon‐snow albedo forcing and snow albedo feedback (climate sensitivity). Key Points: A new snow albedo model for close‐packed snow grains internally mixed with black carbon aerosol is developed Close packing reduces albedos for clean and contaminated snow compared with independent scattering and improves modeled snow albedo BC‐snow albedo effects and albedo feedback are underestimated in climatic analysis and modeling without accounting for snow close packing